The Fundamental Place of Pap Test in Iran, Does Primary HPV-Genotyping Seem Cost-Effective in Replace? A Cohort Study - Azam Zafarbakhsh; Fariba Behnamfar; Matin Shariati; Atefeh Vaezi; Leila Mousavi Seresht (International Journal of Preventive Medicine)
Background: Human papillomavirus (HPV) is a known risk factor for cervical cancer, and currently, primary HPV typing is recommended for screening instead of cervical cytology. However, there are limited studies on the prevalence of HPV in Iran. Methods: This cross-sectional study evaluated the liquid-based cervical smears of 700 women with no history of HPV vaccination and cervical dysplastic disease from 2017 to 2020 in Isfahan, Iran. Here, we compare the prevalence of HPV genotypes using COBAS with Pap smear cytology results in evaluating the most appropriate cervical cancer screening test. Results: The prevalence of HPV infection was 23.3%, including 8.7% with HPV 16/18 and 14.6% with other HR (high-risk) HPVs. In cytology reports, 8 out of 16 individuals with high-risk lesions were negative for any type of HPV; on the other hand, there were 129 HR HPV-positive patients out of 570 negative or low-risk Pap smear results. Conclusions: It assumed that there is no superiority for HPV genotyping over cytology or vice versa in detecting high-risk patients for cervical cancer; as only 26.8% of women with HPV show abnormal cytology; and from those with normal cytology, 17.9% were positive for HR HPV.